Mechanisms of cross-boundary learning : communities of practice and job crafting /: communities of practice and job crafting. (2019) - Ishiyama, Nobutaka; Nakanishi, Yoshinobu; Koyama, Kenta; Takeshita, Hiroshi
No abstract available